2016
DOI: 10.1007/s10579-016-9355-6
|View full text |Cite
|
Sign up to set email alerts
|

The ALICO corpus: analysing the active listener

Abstract: The ALICO corpus: analysing the active listener. Abstract The Active Listening Corpus (ALICO) is a multimodal data set of spontaneous dyadic conversations in German with diverse speech and gestural annotations of both dialogue partners. The annotations consist of short feedback expression transcriptions with corresponding communicative function interpretations as well as segmentations of interpausal units, words, rhythmic prominence intervals and vowel-to-vowel intervals. Additionally, ALICO contains head gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Like Malisz et al (2016), we also found that nods more commonly occurred in groups than one-by-one, see Table 2. Malisz et al (2016) also found the same pattern for head shakes, which we do not significantly see in our corpus.…”
Section: What Modalities Are Most Commonly Used To Convey Negative and Positive Feedback?supporting
confidence: 59%
See 2 more Smart Citations
“…Like Malisz et al (2016), we also found that nods more commonly occurred in groups than one-by-one, see Table 2. Malisz et al (2016) also found the same pattern for head shakes, which we do not significantly see in our corpus.…”
Section: What Modalities Are Most Commonly Used To Convey Negative and Positive Feedback?supporting
confidence: 59%
“…In a multimodal study of the ALICO corpus, Malisz et al (2016) found that listeners used head movements twice as often as speech in response to being told a story by a speaker. Additionally, nods are by far the most common head movement feature, and multiple nods are twice as common as single nods.…”
Section: Head Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult-adult interactions have been extensively studied in the ALICO and MultiLis corpora. ALICO aimed to capture the spoken and gestural dynamics of storyteller-listener dialogue [23]. MultiLis focused on identifying individual differences and similarities of listener responses by having three listeners simultaneously interact with the same speaker [11].…”
Section: Applications In Educational Interactive Technologiesmentioning
confidence: 99%
“…Body movements have been cited as contributing to the coordinated process of social collaboration in a variety of ways. Turn-taking research indicates that people deploy a broad scope of body movements to yield or take the floor, such as pointing gestures (Goodwin 2000; Mondada 2007; Sikveland and Ogden 2012), head movements (Cerrato and Skhiri 2003; Duncan 1972; Hadar et al 1985; Malisz et al 2016; Rahayudi et al 2014), eye gaze (Bavelas et al 2002; Bavelas 2005; Brône et al 2013; Jokinen 2009; Peters et al 2005), prevocal preparations like mouth openings (Streeck and Hartge 1992), and body posture (Holler and Kendrick 2015). Beyond turn-taking, evidence shows that body movements when coupled with speech (co-verbal gestures, such as iconic and other representational gestures; Mittelberg and Evola 2014) provide information not present at the speech level which is successfully decoded by the observer–listener (Kendon 2015; McNeill 1992), even during speech-gesture mismatches (McNeill et al 1994).…”
Section: Introductionmentioning
confidence: 99%